1995
DOI: 10.1212/wnl.45.3.482
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome C Oxidase in Alzheimer's Disease Brain

Abstract: Cytochrome c oxidase (COX) is deficient in both peripheral tissue and brain of Alzheimer's disease (AD) patients and may be of pathogenic significance in AD. We purified COX from AD brains (n = 3) and control brains (n = 3) and characterized the enzyme kinetically and spectrally. Purified AD brain COX displayed anomalous kinetic behavior compared with control brain COX in that the low Km binding site was kinetically unidentifiable. For purposes of comparison, we purified COX from a standard beef heart preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(84 citation statements)
references
References 10 publications
5
77
0
2
Order By: Relevance
“…Our original intent to use Complex III activity as an internal control would have been effective (Barrientos, 2002); Complex I could be used, but it tends to be the most difficult complex to assay and results were not available for every subject. Our Western data, as well as previous literature reports (Parker et al, 1990(Parker et al, , 1994aParker and Parks, 1995), support the contention that Complex IV is catalytically abnormal in AD while protein levels remain normal; it remains unproven what effect that would have on Complex III, if Complex III itself were not also abnormal but subsequently downregulated, or vice versa. While Parker and Parks (1995) characterized a specific catalytic abnormality in Complex IV, the same type of analysis has not been performed on Complex III.…”
Section: Discussionsupporting
confidence: 89%
“…Our original intent to use Complex III activity as an internal control would have been effective (Barrientos, 2002); Complex I could be used, but it tends to be the most difficult complex to assay and results were not available for every subject. Our Western data, as well as previous literature reports (Parker et al, 1990(Parker et al, , 1994aParker and Parks, 1995), support the contention that Complex IV is catalytically abnormal in AD while protein levels remain normal; it remains unproven what effect that would have on Complex III, if Complex III itself were not also abnormal but subsequently downregulated, or vice versa. While Parker and Parks (1995) characterized a specific catalytic abnormality in Complex IV, the same type of analysis has not been performed on Complex III.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to these disease hallmarks, a consistent pattern of changes in mitochondrial morphology and function is detected in AD at an early stage. For example, there is a decrease in the number of mitochondria in vulnerable neurons accompanied by increase in mitochondrial DNA (mtDNA) and protein in cytoplasm and vacuoles, indicating a greater turnover of mitochondria by autophagy or decreased proteolytic turnover [2]; brain glucose metabolism is decreased [3]; and the activities of both tricarboxylic acid (TCA) cycle enzymes [4] and cytochrome c oxidase (COX) are reduced [5][6][7][8]. Recently it was also shown that the levels of mitochondrial fission/fusion proteins are altered and that mitochondria are redistributed away from axons in pyramidal neurons of AD brain [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that mitochondrial A␤ accumulation impairs neuronal function and, thus, contributes to cellular dysfunction in a transgenic APP mouse model (13). It is noteworthy that in AD at an early stage there is already a reduction in the number of mitochondria (14), the brain glucose metabolism is decreased (15), and the activities of both tricarboxylic acid cycle enzymes (16) and cytochrome c oxidase (COX) are reduced (17)(18)(19)(20). In vitro studies with isolated mitochondria suggest that A␤ 1-42 inhibits COX activity in a copper-dependent manner (21).…”
mentioning
confidence: 99%